Kraken reveals itself: the merger history of the Milky Way reconstructed with the E-MOSAICS simulations - Kruijssen, Diederik; Pfeffer, Joel L.; Chevance, Mélanie; Bonaca, Ana; Trujillo-Gomez, Sebastian; Bastian, Nate; Reina-Campos, Marta; Crain, Robert A.; Hughes, Meghan E. (Monthly notices of the Royal Astronomical Society, 2020)
Globular clusters (GCs) formed when the Milky Way experienced a phase of rapid assembly. We use the wealth of information contained in the Galactic GC population to quantify the properties of the satellite galaxies from which the Milky Way assembled.
Advance access publication 2020 August 17
Gesehen am 24.11.2020